Clival fibrous dysplasia in which short interval disease progression posed a diagnostic challenge in a skeletally mature patient: a case report - Sujitra Tinnut; Nancy Pham; Jayakar Nayak; Juan C. Fernandez-Miranda; Hannes Vogel; Nancy Fischbein (Journal of Medical Case Reports)
Abstract Background Fibrous dysplasia is an uncommon bone disorder in which medullary bone is replaced by disorganized fibro-osseous tissue. Fibrous dysplasia typically exhibits slow growth that stabilizes with skeletal maturity. We report a case in which rapid progression of a clival lesion otherwise typical for fibrous dysplasia in an adult male led to concern for a malignant rather than a benign lesion. Case presentation A 38 year-old white male developed eye pain, and magnetic resonance imaging of the brain was interpreted as normal. A total of 2 years later, the patient again presented with eye pain, and a repeat magnetic resonance imaging study demonstrated interval development of a lesion replacing much of the clivus. Though the lesion appeared fairly typical of fibrous dysplasia, with magnetic resonance imaging and subsequent computed tomography revealing a well-defined and mildly expansile clival lesion, lesions of fibrous dysplasia do not typically appear in skeletally mature patients, and they are generally indolent. On the basis of concern for malignant degeneration or possibly an alternative diagnosis, as the patient had been referred to our center with a diagnosis of clival chordoma, the lesion was treated with endoscopic resection. The diagnosis of typical fibrous dysplasia was ultimately confirmed through histopathological, immunohistochemical, and genetic analysis. Conclusion This case demonstrates the potential for development and progression of benign fibrous dysplasia lesions beyond skeletal maturity, a phenomenon rarely reported in literature and not previously demonstrated in the clivus.